Heterogeneous distribution of substrates between the endocardium and epicardium promotes ventricular fibrillation in arrhythmogenic right ventricular dysplasia/cardiomyopathy. Issue 3 (11th January 2017) - Lin, Chin-Yu; Lin, Yenn-Jiang; Li, Cheng-Hung; Chung, Fa-Po; Lo, Men-Tzung; Lin, Chen; Chang, Hsiang-Chih; Chang, Shih-Lin; Lo, Li-Wei; Hu, Yu-Feng; Chang, Yao-Ting; Lin, Chung-Hsing; et al.
Abstract: Aims: Whether the distribution of scar in arrhythmogenic right ventricular cardiomyopathy (ARVC) plays a role in predicting different types of ventricular arrhythmias is unknown. This study aimed to investigate the prognostic value of scar distribution in patients with ARVC. Methods and results: We studied 80 consecutive ARVC patients (46 men, mean age 47 ± 15 years) who underwent an electrophysiological study with ablation. Thirty-four patients receive both endocardial and epicardial mapping. Abnormal endocardial substrates and epicardial substrates were characterized. Three groups were defined according to the epicardial and endocardial scar gradient (<10%: transmural, 10–20%: intermediate, >20%: horizontal, as groups 1, 2, and 3, respectively). Sinus rhythm electrograms underwent a Hilbert–Huang spectral analysis and were displayed as 3D Simultaneous Amplitude Frequency Electrogram Transformation (SAFE-T) maps, which represented the arrhythmogenic potentials. The baseline characteristics were similar between the three groups. Group 3 patients had a higher incidence of fatal ventricular arrhythmias requiring defibrillation and cardiac arrest during the initial presentation despite having fewer premature ventricular complexes. A larger area of arrhythmogenic potentials in the epicardium was observed in patients with horizontal scar. The epicardial-endocardial scar gradient was independently associated with the occurrence of fatal ventricular arrhythmias after a multivariate adjustment. The total, ventricular tachycardia, and VF recurrent rates were higher in Group 3 during 38 ± 21 months of follow-up. Conclusion: For ARVC, the epicardial substrate that extended in the horizontal plane rather than transmurally provided the arrhythmogenic substrate for a fatal ventricular arrhythmia circuit.